Aspects of sintering of cemented carbides with Fe-based binders. (March 2015) - Schubert, W.D.; Fugger, M.; Wittmann, B.; Useldinger, R.
Abstract: Since the early days of industrial production alternative alloy binders for cemented carbides were a focus of research. However, cobalt based alloys turned out to be the most versatile solution for the emerging widespread industrial applications. The paper presents and discusses own results on hardness, toughness, strength, wear resistance, hot hardness and creep of iron-based cemented carbides in comparison to conventional cobalt alloys; based on three iron binder systems: (a) FeNi = 90/10, 85/15, 80/20 and FeCoNi = 70/10/20, respectively (austenitic/martensitic) (b) Fe/Ni/Co = 40/40/20 (austenitic) (c) Fe/Mn (ferritic/austenitic). Vertical sections provided by CALPHAD calculations showed a good agreement with our experiments and provides a deeper understanding of the metallurgical changes occurring on the substitution of Co by Fe and Ni. Highlights: The work discusses the substitution of cobalt in cemented carbides by iron-nickel and iron-nickel-cobalt. Three steel-binder grades are presented: grades with a metastable austenitic binder (FeNi, FeNiCo); grades with a stable austenitic binder (FeNiCo); and grades with a Hadfield binder (FeMn). Crucial aspects are discussed with regard to the phase constitution of the respective systems.